Effect of Vacuum on Evaporation of Seawater - Yusuf, Ahmad Maulana; Dan Mugisidi; Ikbal Prasetiyo Aji; Oktarina Heriyani (Universitas Muhammadiyah Sidoarjo, 2023)
Water has become a vital necessity for every living organism to survive, leading to a threefold increase in global freshwater usage over the past 50 years. However, only 2.8% of the Earth's surface water is freshwater, while the rest is seawater. Therefore, seawater is processed into clean freshwater through desalination methods to make it consumable for the public. The desalination process involves two stages: evaporation and condensation aided by heat energy from a heater plate and a vacuum system. The use of vacuum in the desalination device aims to accelerate evaporation. In this study, three vacuum pressure variables were tested, namely no vacuum, 1 inHg vacuum pressure, and 2 inHg vacuum pressure. Data will be collected every 5 minutes for a total duration of 30 minutes for each variable. The research findings indicate that desalination using a vacuum system significantly affects the evaporation rate and the amount of freshwater obtained from the condensation process.